Association and Interaction Between Serum Interleukin-6 Levels and Metabolic Dysfunction-Associated Fatty Liver Disease in Patients With Severe Coronavirus Disease 2019 - Gao, Feng; Zheng, Kenneth I.; Yan, Hua-Dong; Sun, Qing-Feng; Pan, Ke-Hua; Wang, Ting-Yao; Chen, Yong-Ping; Targher, Giovanni; Byrne, Christopher D.; George, Jacob; Zheng, Ming-Hua (Frontiers in Endocrinology, 2021)
Background & Aim: Circulating levels of interleukin (IL)-6, a well-known inflammatory cytokine, are often elevated in coronavirus disease-2019 (COVID-19). Elevated IL-6 levels are also observed in patients with metabolic dysfunction-associated fatty liver disease (MAFLD). Our study aimed to describe the association between circulating IL-6 levels and MAFLD at hospital admission with risk of severe COVID-19. Methods: A total of 167 patients with laboratory-confirmed COVID-19 from three Chinese hospitals were enrolled. Circulating levels of IL-2, IL-4, IL-6, IL-10, tumor necrosis factor (TNF)-α, and interferon (IFN)-γ were measured at admission. All patients were screened for fatty liver by computed tomography. Forty-six patients were diagnosed as MAFLD. Results: Patients with MAFLD (n=46) had higher serum IL-6 levels (median 7.1 [interquartile range, 4.3-20.0] vs. 4.8 [2.6-11.6] pg/mL, p=0.030) compared to their counterparts without MAFLD (n=121). After adjustment for age and sex, patients with MAFLD had a ~2.6-fold higher risk of having severe COVID-19 than those without MAFLD. After adjustment for age, sex and metabolic co-morbidities, increased serum IL-6 levels remained associated with higher risk of severe COVID-19, especially among infected patients with MAFLD (adjusted-odds ratio 1.14, 95%CI 1.05-1.23; p=0.002). There was a significant interaction effect between serum IL-6 levels and MAFLD for risk of severe COVID-19 (p for interaction=0.008). Conclusions: Patients with MAFLD and elevated serum IL-6 levels at admission are at higher risk for severe illness from COVID-19.